2021
DOI: 10.3892/etm.2021.10413
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis beyond the skin: Ophthalmological changes (Review)

Abstract: Psoriasis is a chronic, immune-mediated inflammatory disease of unknown etiology that may be associated with abnormal T-lymphocyte function. Ocular manifestations associated with psoriasis, particularly artropathic or pustular psoriasis, usually affect men, often during exacerbations of the disease. It has been reported that eye damage tends to occur later compared with cutaneous or joint manifestations, blindness being the most disabling complication. Previous studies have focused on ophthalmic manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
13

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
0
11
0
13
Order By: Relevance
“…We could not find any association between ocular manifestation and clinical type of psoriasis which might be due to insufficient number of cases of different clinical types and also absence of some types such as pustular or erythrodermic variants which have been shown to be associated with severe dry eye syndrome in psoriasis patients. 4 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We could not find any association between ocular manifestation and clinical type of psoriasis which might be due to insufficient number of cases of different clinical types and also absence of some types such as pustular or erythrodermic variants which have been shown to be associated with severe dry eye syndrome in psoriasis patients. 4 …”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 Previous studies have shown some ocular manifestations in patients with psoriasis, especially those with arthropathic or pustular variants of the disease. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiological relationship between uveitis and psoriasis has not been fully elucidated; regardless, uveitis has been frequently observed in cases of psoriasis vulgaris and PsA, especially among men [ 1 , 5 , 10 13 ], mainly with HLA-B27 positivity [ 14 ]. Tanaka et al [ 15 ] reported an unusual distribution of uveitis in Japanese patients, being most common in psoriasis vulgaris (7/13) than in PsA (4/13).…”
Section: Discussionmentioning
confidence: 99%